factorise this Question
Q1 ) 6x^2+5x-6
Answers
Answered by
1
Here is the answer of your question
Attachments:
![](https://hi-static.z-dn.net/files/de5/ca5ef5842ef7a54c019a644c990111f7.jpg)
Answered by
1
Answer:
The factors of 6x² - 5x- 6 are (2x-3) (3x+2)
Step-by-step explanation:
Step 1: Multiply the coefficient of the first term by the constant term i.e (6 x -6) = -36
Step 2: Find the two factors of -36 such that it's sum is equal to the coefficient of the middle term, i.e -5 .
Hence, two such factors are -9 and 4
-9 × 4 = -36 (Product)
-9 + 4 = -5 (Sum)
Thus, by splitting the middle term we have,
6x² - 9x + 4x - 6=0.
⇒ 3x(2x-3) + 2(2x-3) = 0
⇒ (2x-3)(3x+2) = 0
Thus, the factors of 6x² - 5x - 6 are (2x-3) (3x+2).
Similar questions
World Languages,
1 month ago
Biology,
1 month ago
Math,
3 months ago
Math,
3 months ago
Math,
11 months ago